Model Pembelajaran Efektif di Era Pandemi Covid-19 Meningkatkan Hasil Belajar Siswa SDN Kubang Sepat 2 Cilegon - Ramadhanti, Marsya Afifa; Yasmin, Najwan Dennisa; Zahra, Zairah (MASALIQ, 2022)
The background of this research is the problem that there is no use of the right learning model. the use of media that is less varied, in the teaching and learning process the teacher has not been able to create active and fun learning, students are less interested in the learning provided by the teacher. The purpose of this research is to describe the implementation, understanding of student learning concepts in learning. The method in this study uses an action research model which was developed through four stages, namely: planning, action, observation, and reflection. The flow of this research was carried out in two cycles. The results of the research show that the application, approach to learning models can analyze the learning process, the activeness of students in the learning process increases